Antecedents and consequences of psychological contract breach. Issue 8 (14th November 2016) - Peng, J.C.; Jien, Jia-Jing; Lin, Julian
Abstract : Purpose: The purpose of this paper is to investigate store-level servant leadership and the procedural justice climate (PJC) as key antecedents for employee-perceived psychological contract breach (PCB) and explores the mediating roles of PCB in the relationships among servant leadership, the PJC and deviant employee behavior. Design/methodology/approach: Survey data were collected from 301 employees at 94 stores of a restaurant chain in Taiwan. The model and hypotheses were tested using hierarchical linear modeling. Findings: The results support the moderated mediation model, showing that the indirect effects of servant leadership and PJC on deviant employee behavior through PCB were stronger for employees with an external locus of causality attribution than for those with an internal locus. Research limitations/implications: The study relied on cross-sectional survey design, therefore the authors cannot infer causality. Practical implications: The results will help organizations and managers understand that supervisor servant leadership has suppressive effects on deviant employee behavior through the intermediary mechanism of negative psychological perception (i.e. the perception of a PCB). Originality/value: The primary purpose of this study is to examine the influences of store-level servant leadership and the PJC on employee deviance and to examine the mediating role played by PCB. The findings suggest a significantly negative relationship.